A National Health Service : The White Paper proposals in brief - Great Britain. Department of Health for Scotland (London : His Majesty's Staionery Office, 1944)
1944 1944 1940s 32 pages for every Joint Board area, a Local Medical Services Committee. The Committees will be to some extent similar to the Councils, but they will have a wider function. It will be their duty both to advise the Secretary of State on the development of the general practitioner service — the need for Health Centres, for example — and to act as a means of liaison between the general practitioner service and the other parts of the health service. With these wider functions in view it is proposed that the Local Medical Services Committees shall consist of representatives of all the major local authorities in the area, of the local medical, dental, pharmaceutical and nursing professions, and of other interests closely concerned with the health services. VIII FINANCE Cost to public funds It is not possible within the limits of a short paper to explain in detail how the new Health Service will be financed ; for that, reference must be made to the White Paper itself. But the present paper would not be complete if it did not give some indication of the scale of expenditure involved and of how it will be met. It is estimated that in England and Wales the total annual cost of the National Health Service to public funds will be not less than £132 millions, as compared with about £55 millions from public funds spent on the present health services. Of this sum of £132 millions about £70 millions will be spent by the new joint authorities on the hospital, consultant and other services which they will provide and maintain themselves, including payments made to voluntary hospitals for their services under the area plan. About £22 millions will be spent by county and county borough councils on the services for which they are to be directly responsible. The State will itself spend directly about £30 millions on the new general practitioner service — including payments to chemists. (The remaining £10 millions is the part of the expenditure of voluntary hospitals which will be met by a direct grant from the State.) State grants Apart from its own direct expenditure on the general practitioner service, the State will give grants to local authorities and to voluntary hospitals. The arrangements proposed are as follows :— (1) A hospital grant of £100 a bed (£35 in mental hospitals and infectious disease hospitals, because of their lower comparative costs and because the scheme broadly does not impose any 26 36/H24/41